Effects of Planting Methods and Varieties on Rice Quality in Northern China - Lili Wang; Liying Zhang; Na He; Changhua Wang; Yuanlei Zhang; Zuobin Ma; Wenjing Zheng; Dianrong Ma; Hui Wang; Zhiqiang Tang (Foods)
With the continuous improvement in living standards, consumers’ demand for rice quality has been increasingly growing. This study analyzed the quality characteristics of different rice varieties under various cultivation methods. This study examined the rice variety Liaoxing 21 (LX21), the upland rice variety Han 9710 (H9710), and the hybrid rice variety Liaoyou 7362 (LY7362) from Liaoning Province to evaluate the effects of transplanting (TP) and direct seeding (DS) on processing, appearance, nutritional, and tasting quality. The results indicated that the planting method (PM) had a relatively minor impact on processing quality. Compared to TP, DS significantly increased grain length (GL) by 1.19%, grain width (GW) by 2.69%, appearance (A) by 2.61%, stickiness (Ss) by 7.15%, degree of balance (DB) by 3.19%, apparent amylose content (AAC%) by 6.20%, fa by 0.66%, fa/fb3 by 5.34%, and protein content (PC) by 19.93%. However, DS significantly reduced the grain length/width ratio (GL/W) by 1.03%, chalky grain rate (CGR) by 46.00%, chalkiness (CH) by 52.76%, and fb3 by 4.23%. Compared to DS, TP resulted in a higher peak viscosity (PV), final viscosity (FV), and pasting temperature (PaT), whereas setback (SB) was lower. Among the tested varieties, LX21 exhibited superior milled rice rate (MRR), head rice rate (HRR), GL, GL/W, A, Ss, DB, taste value (T), and FV compared to H9710 and LY7362, while demonstrating significantly lower CGR, CH, hardness (H), fa, trough viscosity (TV), and peak time (PeT). Under the same planting conditions, the conventional rice variety LX21 demonstrated excellent processing, appearance, and taste quality, whereas H9710 exhibited favorable nutritional quality and Rapid Visco Analyzer (RVA) characteristics. Meanwhile, we also analyzed the correlation between temperature/light conditions and nutritional quality, as well as RVA profiles. The results showed that variations in temperature and light were closely associated with amylopectin accumulation and starch pasting properties. This study highlights the findings that selecting the appropriate PMs and japonica rice varieties can effectively enhance overall rice quality. In the medium maturing regions of Liaoning Province, adopting DS with medium–early maturing japonica rice varieties offers an optimal production strategy for achieving high quality, high yield, and efficient utilization of temperature and light resources.